(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Education plays a vital role in carrying out, sustainingand dispersing the processes of development through its profound impact onsocio-economic, cultural and political framework of a nation. The economicdevelopment governs certain basic determinants of education, i.e., educationalinfrastructure, allocation of resources for education and economic base of thehouseholds to support education of their children. Similarly, educationdirectly contributes to the economy through its effects on the determinants ofeconomic development, i.e. productivity,earnings, job mobility, entrepreneurial skills and technological innovations.Therefore, it is one of the most important basic needs and as such a priorityarea for intervention.